Tax Avoidance and Corporate Governance Determine Coal Mining Company Value: Penghindaran Pajak dan Tata Kelola Perusahaan Mempengaruhi Nilai Perusahaan Pertambangan Batubara - Wulandari, Hanifa Putri; Hanun, Nur Ravita (Indonesian Journal of Innovation Studies, 2025)
General Background Sustained corporate value maximization requires sophisticated control systems over financial and non-financial strategies in turbulent industries. Specific Background The Indonesian coal mining sector faces volatile commodity prices (2018–2022) which complicate investor perception of fundamental value drivers (Capital Structure, Profitability) and strategic policies (Tax Avoidance). Knowledge Gap Mixed empirical results exist regarding the simultaneous impact of these factors, especially concerning the role of Good Corporate Governance (GCG) in regulating manager opportunism and agency conflicts within this specific sector. Aims This study aimed to examine the direct relationship of Capital Structure, Profitability, and Tax Avoidance on Company Value, and the moderating function of GCG, using a sample of 75 observations from Indonesian coal mining companies (2018–2022). Results Tax Avoidance is found to be positively and significantly related to Company Value, while Capital Structure and Profitability show negative and insignificant effects. GCG successfully moderates the effect of Tax Avoidance but is unable to strengthen or weaken the influence of the other two factors. Novelty This study provides empirical evidence that GCG’s moderating capability is selective, focusing specifically on tax planning strategy as a driver of firm value in this sector. Implications Management should prioritize careful Tax Avoidance practices under stringent GCG oversight to optimize shareholder value. Highlights: Tax Avoidance demonstrates a positive and significant relationship with Company Value. Capital Structure and Profitability show negative and insignificant effects on Company Value. Good Corporate Governance selectively moderates only the effect of Tax Avoidance. Keywords: Capital Structure, Profitability, Tax Avoidance, Corporate Governance, Company Value